Act or Object: A Time for Argument Theory Differentiation - Butterworth, John (Informal Logic, 2021)
Many standard definitions of ‘argument’ that recognise an ambiguity between its active and objective senses seek to subsume these in various ways into a single, composite whole. This, it is argued, glosses over the distinction instead of exploiting its elucidatory potential. Whilst optimistic about the prospects of theory integration, the paper recommends a methodology of differentiation as a first necessary step towards any such goal. It starts by assuming that ‘argument’ refers —simultaneously and independently— to two different things, making space between them for a theory of argument based on the then necessary externality of the relation between them.